(untitled) (Research, Society and Development, 2021)
The use of natural plant extracts is a very old practice and its use in folk medicine has spread from culture to culture. During the gestational period is when many women end up looking for the use of some plants to alleviate the symptoms that arise during this period, so we sought to analyze the benefits of using ginger (Zingiberofficinale) against the symptoms of the pregnancy period. Ginger, which is a well-known plant and has been widely used, therefore, it served as a study for its powerful antiemetic potential. Therefore, the aim of this study was to carry out an integrative literature review, emphasizing the effectiveness of ginger in relieving symptoms caused by pregnancy. To support the research, SciELO, ScienceDirect, EBSCO and PubMed were used, and the analyzed materials were published between the years 2011 to 2021. It is concluded that with the scientific data obtained, the use of ginger presented satisfactory results that point to a significant reduction in the symptoms of náusea and vomiting during pregnancy.